Are International Codes Of Conduct Effective In Achieving CSR : A Multinational And Sectoral Perspective - Harwood, Cordelia Anne (2003)
Corporate Social Responsibility (CSR) is the new business catchword. Polls show that consumers are increasingly making choices based on ethical grounds1, that managers view irresponsible companies negatively2 and believe meeting social concerns makes business3 and investment sense4. This study sets out to discover whether there is a difference in the way that various companies within the three sectors of the automobile, banking and oil industries approach corporate social responsibility and the motivations for which these industries do so. Unsurprisingly all the industries are getting to grips with the terminology and recognise CSR’s importance for their reputations with consumers and stakeholders. Research reveals that the banking industry is where the most pressure occurs for companies to regulate ‘voluntarily’ and where verification is the norm. Confrontations between stakeholders and multi-nationals that are aired in the media are common to all sectors. Companies with inherent societal and environmental impacts such as the automobile and oil industry can quickly exploit the brand advantage that meeting CSR challenges can give them to forge a place in the future. This ability is clearly dependent on their profitability although it is not necessarily true that profitable companies are more socially responsible. Codes of conducts are increasingly emerging to discourage stricter legislation and to ensure a level playing field for industries.